Equivocality of Factor Incongruence As an Indicator of Type of Change in OD Interventions - Lindell, Michael K.; Drexler, John A. (Academy of Management Review, 1980)
Michael K. Lindell, John A. Drexler, Jr., Equivocality of Factor Incongruence as an Indicator of Type of Change in OD Interventions, The Academy of Management Review, Vol. 5, No. 1 (Jan., 1980), pp. 105-107